The Fighting Frenchman : Minnesota's Boxing Legend Scott LeDoux - Levy, Paul, 1950- (Book collections on Project MUSE., 2016)
"Scott LeDoux's face read like a roadmap of boxing's last golden era--eye thumbed by Larry Holmes, brow gashed by Mike Tyson, ears stung by none other than Muhammad Ali. "George Foreman hit me so hard," LeDoux said, "my ancestors in France felt it." The only man to step into the ring with eleven heavyweight champions, LeDoux also fought through two of boxing's greatest scandals, recurring illness, and childhood trauma that haunted him for decades. This is his story, the life and times of a Minnesota Rocky making the most of the hard knocks that bruise the American Dream, told in full for the first time by award-winning journalist Paul Levy. He was never a world champion, but Scott LeDoux was always the people's champ. Doing his best to turn a small-town miner's son into boxing's next great white hope, Don King said of Scott LeDoux: "He eats rusty nails for breakfast, punches holes in concrete with either hand, bobs and weaves like a giant Rocky Marciano." He was a big, good-natured kid, with a ready wit and the will to take all comers along on a ride he himself found hard to believe. From the mining community of Crosby, Minnesota, to the dingy, mildew-scented dressing rooms in minor-league towns like Sioux Falls and Billings, to the stage of Madison Square Garden, Levy gives us a real sense of what it was like to spar with fighters such as Tyson and Ali. The buried secrets of childhood abuse and the harrowing sadness of death and disease in his family make LeDoux's triumphs and defeats all the more poignant and, in Levy's irresistible narrative, unforgettable"--